Analisis Residu Pestisida dalam Tomat, Cabai Rawit dan Wortel dari Beberapa Pasar Tradisional di Sulawesi Utara - Abdon Saiya; Dokri Gumolung; Joice Dorsila Susana Caroles (Jurnal Kimia Fullerene, 2018)
One method to eradicate plant pests carried out by farmers in the North Sulawesi area is to use pesticides because they are considered easy to obtain, the price is still affordable, and very effective at killing plant pests. However, improper use of pesticides results in the loss of pesticide residues in plants which causes environmental pollution, health problems in humans and inhibits trade. Therefore, it is necessary to monitor the use of pesticides through the fulfillment of the maximum residual limit (BMR). This study aims to analyze pesticide residues in tomatoes, cayenne pepper, and carrots using the method of High Performance Liquid Chromatography (HPLC) which was previously optimized and validated. The research samples were tomatoes, cayenne pepper, and carrots, taken from Pasar Bersehati Tomohon, Pasar Karombasan Manado, and Pasar Kawangkoan Minahasa, then taken to the Chemistry Laboratory of Manado State University to be extracted and analyzed. The results of this study indicate that pesticides with chlorpyrifos active ingredients were detected in almost all samples analyzed, although the levels were still below the specified BMR value, ie 1 mg/kg sample. The highest chlorpyrifos level was found in tomato samples taken from Pasar Kawangkoan Minahasa, which was 0.3150 mg/kg. The results of this study also showed that samples that were washed before extraction caused a decrease in the residual content of the petisides.